2019
DOI: 10.1111/dth.13180
|View full text |Cite
|
Sign up to set email alerts
|

Malignant melanoma in HIV: Epidemiology, pathogenesis, and management

Abstract: People affected by immunodeficiency, and especially those infected by HIV, are burdened by a higher risk of developing malignancies. It has been estimated that the incidence of melanoma in HIV-infected people is 2.6-fold higher than in uninfected ones.In this group of patients, melanoma shows a more aggressive phenotype and poorer survival rates compared to HIV-negative people. Standard guidelines of diagnosis and care do not exist yet. Studies suggest high index of suspicion and a low threshold for biopsy in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 42 publications
(98 reference statements)
0
22
0
Order By: Relevance
“…TNF-a exerts several effects. It could promote the progression of cancer (46), but also blocking TNF-a could result in arresting antitumor immune response and in promoting the growth of immunogenic tumors (47)(48)(49).…”
Section: Discussionmentioning
confidence: 99%
“…TNF-a exerts several effects. It could promote the progression of cancer (46), but also blocking TNF-a could result in arresting antitumor immune response and in promoting the growth of immunogenic tumors (47)(48)(49).…”
Section: Discussionmentioning
confidence: 99%
“…Infection with HIV leads to impaired immunity which might, in turn, result in less effective control of the initiation or progression of skin tumours. Indeed, it is known that CMs in HIV-positive patients are more aggressive and survival rates are poorer than in HIV-negative people [36]. Studies in California demonstrated that there was a greater than two-fold higher incidence of SCC, but not of BCC, in White HIV-positive patients compared with White HIV-negative controls [37,38].…”
Section: Risk Factors For the Development Of Skin Cancer In Southern mentioning
confidence: 99%
“…1,4 Ultraviolet, race, human immunodeficiency virus, gene, and telomere length are important risk factors for melanoma. [5][6][7][8][9] One of the biggest difficulties in clinical treatment is how to evaluate and predict cancer metastasis and death. 10 Specific biomarkers with high sensitivity are the key to solve this problem.…”
Section: Introductionmentioning
confidence: 99%